The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.7717/peerj.4373
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of antioxidative peptides from mackerel (Pneumatophorus japonicus) viscera

Abstract: Mackerel (Pneumatophorus japonicus) viscera contain large amount of protein. We used five proteases to hydrolyze the viscera, and the hydrolysate treated by neutrase exhibited the highest nitrogen recovery (NR). Then we optimized the preparation conditions for mackerel viscera hydrolysate (MVH) by response surface methodology and investigated the antioxidant activity of MVH. The optimal conditions were as follows: enzyme concentration of 1,762.87 U/g, pH of 6.76, temperature of 43.75 °C, extraction time of 6.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
4
0
2
Order By: Relevance
“…Additionally, the cellular antioxidant activity initially increased and then decreased slightly as the X 4 increased from 1 to 9, as shown in Figure 3H,J. We speculated that a higher X 4 may dilute the X 1 and slow the rate of enzyme reactions [22].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the cellular antioxidant activity initially increased and then decreased slightly as the X 4 increased from 1 to 9, as shown in Figure 3H,J. We speculated that a higher X 4 may dilute the X 1 and slow the rate of enzyme reactions [22].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above data, different response values were obtained for hydrolysates generated with different independent variable conditions. In our DH assay study, the DH content of the OP increased significantly when the hydrolysis time increased from 5.0 h to 6.0 h and decreased significantly with a hydrolysis time from 6.0 h to 7.0 h. This trend was consistent with the results of Wang et al [ 12 ], which showed that the DH of fish gelatin hydrolysate increased significantly ( p < 0.05) when the time increased from 1.0 h to 2.0 h, and decreased slowly when the time increased from 2.0 h to 3.0 h. We inferred that the hydrolysis reaction was powerful in the first few hours because of the sufficient raw material and enzyme quantity, and the reaction flattened later with the consumption of raw material and protease [ 19 ]. Some studies have come to different conclusions; for example, Zheng et al [ 20 ] found that the DH value obtained from alcalase increased rapidly during the first 2.0 h of the reaction and then slowly increased, while the hydrolysates obtained from bromelain achieved an obvious increase after 2.0 h. Tan et al [ 21 ] found that the DH of cod bone protein increased rapidly during the first 0.5 h because more peptide bonds were broken, and then the DH showed a slow increase.…”
Section: Discussionmentioning
confidence: 99%
“…The DPPH scavenging activity was assessed following the method described by Paul et al [ 29 ]. Briefly, a mixture of 1 mL JPHT-2 solution and 1 mL DPPH solution (0.1 mM in ethanol) was prepared and incubated at room temperature for 30 min in the absence of light.…”
Section: Methodsmentioning
confidence: 99%